Characterization and gas transport properties of UV-irradiated polydimethylsiloxane (PDMS)-containing polyimide copolymer membranes. (1st December 2020) - Park, Jaesung; Gaines, Kyle E.; Jheng, Li-Cheng; Riffle, Judy S.; Mecham, Sue J.; McGrath, James E.; Park, Ho Bum; Paul, Donald R.; Freeman, Benny D.
Abstract: The influence of UV irradiation on gas permeation properties of random segmented poly (imide-siloxane) (PIS) copolymer films was investigated. Random segmented copolymers were synthesized via ester-acid imidization from 4, 4'-(hexafluoroisopropylidene)diphthalic anhydride (6FDA) and 3, 3′, 4, 4′-benzophenone tetracarboxylic dianhydride (BTDA) in a 7:3 M ratio with 2, 4-diamino mesitylene (DAM) and varying amounts of a diamine terminated polydimethylsiloxane (PDMS) oligomer ( M n  = 3000 g/mol). Solvent cast films of these copolymers were UV-irradiated on both sides in air at 365 nm, which induced crosslinking and photooxidation. Pure-gas permeabilities of H2, O2, N2, CH4, and CO2 were measured with upstream pressures ranging from 2 to 18 atm at 35 °C. Gas permeability coefficients of a series of PIS copolymers decreased, and selectivity of all gas pairs increased after UV irradiation due to a decrease in free volume by UV crosslinking and photooxidation. Graphical abstract: Image 1 Highlights: Polydimethylsiloxane (PDMS)-containing polyimide copolymers were crosslinked by UV irradiation. Gas permeability decreases and selectivity increases after UV irradiation. An improvement in selectivity after UV irradiation pushes the O2 /N2 transport properties closer to the 2008 upper bound.